The Influence of Anxiety Factors on the Smooth Production of Breast Milk in Postpartum Mothers - Sumyati, Yeti; Sutarno, Maryati (Indonesian Journal of Global Health Research, 2024)
The World Health Organization (WHO) and the United Nations International Children's Emergency Fund (UNICEF) have recommended exclusive breastfeeding for at least the first 6 months of life. However, the coverage of exclusive breastfeeding in Indonesia is still not perfect. This is caused by various factors such as stress, pressure, unease, anxiety, sadness, and tension will affect the smoothness of breast milk. The aims of this study was to analyze the effect of anxiety factors on the smooth release of breast milk in postpartum mothers. This research is a type of cross-designed intervention research in Sangkanmanik Village in September 2023. The population in this study was 68 people. The sampling technique uses total sampling. The independent variable of the study was anxiety. The instrument to measure anxiety is the HARS (Hamilton rating scale) questionnaire. The bivariate analysis used in this study was the Chi-Square test. In the bivariate chi square analysis, it was shown that there was a significant and meaningful relationship between anxiety and smooth breast milk expenditure because the p value results were 0.002 < 0.05.